Commentary on Matthew - Hilary, Saint, Bishop of Poitiers, -367? (Book collections on Project MUSE., 2013)
"When the writing of Latin biblical commentaries was still in its infancy, a young bishop from Poitiers, in Gaul, penned a passage-by-passage exposition on the Gospel of Matthew. It is the first of its kind to have survived almost completely intact. Published now for the first time in English translation, Hilary's commentary offers a close look at Latin theology and exegesis before the Nicene Creed was considered the sole standard of orthodoxy. Likely the earliest of Hilary's writings, this commentary has none of the polemic against the "Arians" that figured so prominently in most of his later works. Nonetheless, there exists in this text an oft-stated concern with those who interpreted the Incarnation as grounds for construing Christ as only a man rather than professing Christ as God and man. Other noteworthy features of the commentary include Hilary's interest in the relation between Law and Gospel and his articulation of a Pauline-based view of justification by faith. In his view, the importance of the Law before the Gospel was indisputable and necessary. For Jews, it was considered the way of redemption. With the advent of Christ, it became an eschatological guide directing all future believers into the grace that comes by faith. Hilary's emphasis on God's righteousness conferred on a helpless race represents a far more pronounced application of Paul's thought than in any previous Latin writer"--Provided by publisher